2003
DOI: 10.1097/01.ogx.0000093273.38442.be
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Early-Onset Group B Streptococcal Disease in the Era of Intrapartum Chemoprophylaxis: Residual Problems

Abstract: Apart from their key role in immunologic signaling, cytokines are thought to play a part in ovulation, implantation, placentation, and parturition. There is mounting evidence that cytokines can contribute to preterm births associated with intrauterine infection. This study measured levels of cytokines produced by maternal peripheral blood mononuclear cells after stimulation by mitogen, autologous placental cells, and an extract of trophoblast antigen. Cytokine levels were compared in 30 women admitted in activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…False-negative results may be the consequence of inconsistent policies for prevention (ie, use of cervical or vaginal rather rectovaginal sampling or culture on nonselective broth media). Pinto et al 15 found that, of 92 mothers of infants with EOD, 22 had been GBS screened. Eighteen of 22 were culturenegative because of suboptimal culture techniques or because maternal swabs were collected Ͼ6 weeks before delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…False-negative results may be the consequence of inconsistent policies for prevention (ie, use of cervical or vaginal rather rectovaginal sampling or culture on nonselective broth media). Pinto et al 15 found that, of 92 mothers of infants with EOD, 22 had been GBS screened. Eighteen of 22 were culturenegative because of suboptimal culture techniques or because maternal swabs were collected Ͼ6 weeks before delivery.…”
Section: Discussionmentioning
confidence: 99%
“…However, EOD may occur in infants born to GBS-negative women even if screening is appropriate. 15,16 In a retrospective analysis of 25 EODs, Puopolo et al 17 found that 14 of 17 mothers of term infants affected by disease did not receive prophylaxis because they were screened negative for GBS. Recently it has been observed that the rate of maternal GBS carriage could be considerably higher than that predicted by late antenatal cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these were case series of infants with early-onset GBS disease. [17][18][19][20][21][22] One excluded study was a casecohort design, which had an inadequate number of cases with data on intrapartum prophylaxis. 23 Three excluded studies were clinical trials in which duration of intrapartum prophylaxis was reported for only 8, 13, and 2 patients, respectively.…”
Section: Study Methodology and Qualitymentioning
confidence: 99%
“…Numerous residual problems, barriers to implementation, and missed opportunities must be overcome to achieve maximal benefit from IAP [651][652][653]. Procedural issues, such as suboptimal culture processing and collection of cultures earlier than 5 weeks before delivery, constitute one set of problems.…”
Section: Intrapartum Antibiotic Prophylaxismentioning
confidence: 99%